Uji Sifat Fisik Dan Aktivitas Antibakteri Krim Ekstrak Etanol Daun Bidara (Ziziphus Spina-Christi L.) Terhadap Propionibacterium Acnes ATCC 6919 - Monik Krisnawati (Journal of Health (JoH), 2021)
Acne is a chronic inflammatory disease of the polysebaceous region characterized by the appearance of comedones, papules, pustules, nodules, and cysts. Bidara contains phenolics and flavonoids which are useful as anti-inflammatory, antioxidant, antimicrobial, and prevent tumors. Other chemical constituents of Bidara that play a role in treatment are alkaloids, phenols, flavonoids, and terpenoids. This study aims to determine the effect of the concentration of the ethanolic extract of Bidara leaves (Ziziphus-Spina Christi L.) on the physical properties of the cream and the antibacterial activity of the Bidara leaf cream against the bacteria Propionibacterium acnes ATCC 6919 made in type O/W (Oil in Water) using a vanishing cream with 3 kinds of concentration, namely 10%, 12.5%, and 15%. Physical properties (organoleptic, spreadability, adhesion, and protection) and antibacterial activity against Propionibacterium acnes were measured using the well diffusion method. The results of the test of physical properties and antibacterial activity were analyzed using statistical tests with a 95% confidence level. The results of the physical properties test showed that the cream of ethanol extract of Bidara leaves had the aroma of Bidara leaves, greenish color, semisolid form, and homogeneous texture. The cream of ethanol extract of Bidara leaves with a concentration of 15% showed the greatest dispersion and adhesion at 6.9 cm and 6 seconds. The protection ability of bidara ethanol extract cream at the overall concentration was shown up to 5 minutes.